Capability Factor Identification and Influence Assesment on Supply Chain Resilience in Indonesian Automotive Industry - Munikhah, I Anna Tul; Ramdhani, Ade Yanyan (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2022)
The Automotive Industry is one of the business lines affected by the COVID-19 pandemic in Indonesia. The pandemic causes instability in the Indonesian economy from demand and sales. The supply chain is a long process consisting of parties involved directly or indirectly in fulfilling customer needs: suppliers, manufacturers, shipping, warehouses, checking, and the customers themselves. In an increasingly dynamic and volatile global environment, various events threaten to disrupt supply chain operational activities. For example, the COVID-19 pandemic has caused supply chain management to be very vulnerable due to closing access and lockdown policy. Therefore, the designed supply chain system must withstand disruptions and recover quickly at a minimal cost. Supply Chain Resilience (SCR) is the ability of the supply chain to survive, adapt, and overcome operational disruptions that can damage the supply chain system so that the supply chain can quickly recover from disruptions and reconstruct the supply chain to be stronger than before. SCR has attributes that enable companies to anticipate and overcome disruptions. The Automotive Industry in Indonesia needs to identify what capabilities have been or will be used to anticipate supply chain disruptions which are then quantified to find out which capabilities have the most effect on increasing supply chain resilience. The method used in this study is DEMATEL (Decision Making Trial And Evaluation Laboratory) - ANP (Analytic Network Process) based, which can visualize causal relationships between factors through a cause-and-effect diagram and show the extent to which these factors influence each other.